Uji Aktivitas Antimikroba Ekstrak Metanol Daun Tabat Barito ( Ficus deltoidea Jack) - Krisyanella Krisyanella; Meri Ardianti; Dachriyanus Dachriyanus (Jurnal Farmasi Higea, 2009)
An antimicrobial activity studies from methanol extract of the leaves Tabat Barito (Ficus deltoidea Jack) to some bacterias and fungis with diffusion method and determination of Minimum Inhibitory Consentration (MIC) by using dilution method have been done. From antimicrobial activity test by using diffusion method show that methanol extract of the leaves Tabat Barito (Ficus deltoidea Jack) can inhibit the growth of bacterias and fungis. The MIC for staphylococcus aureus is 1%, for staphylococcus epidermis is 0.7%, for staphylococcus aeruginosa is 0.8%, and for eschericha coli is 0.7%.